A STUDY ON IMPLICATURE IN THE MAIN CHARACTER’S UTTERANCE OF MEGAMIND MOVIE USING RELEVANCE THEORY - WIDODO, EMIL GOZA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Implicature, Relevance Theory, and MovieImplicature is what the addresser wants to convey without stating it explicitly. In this study, the writer intends to analyze an implicature in Megamind Movie  using  Relevance Theory.  This study is conducted to find out (1) the explicature conveyed in the utterances of the main character in Megamind movie. (2) The implicated premises and implicated conclusion conveyed in the utterances of the main character in Megamind movie. The writer uses Sperber and Wilson’s theory in analyzing the data.This study is qualitative study since the writer analyzed utterances taken from the dialogue of the main characters in Megamind Movie. Research design is document  analysis.  From the  data  obtained,  the  writer  tried  to  find  out  the explicature,  implicated premise,  and implicated conclusion based on Relevance Theory proposed by Sperber and Wilson (1995).In this study the writer found 14 utterances that convey an implicature. To answer research problem the writer gave an example from the conversation that were taken from datum 2. The context of this conversation is when Megamind crashing Metroman’s Memorial Day by kidnapping Roxanne Ritchi. Metroman is threatening Megamind to put him into jail by saying We all know how this ends, with you behind the bars. The word ‘we’ refers to Metroman and all the citizen of Metro city, while ‘this’ refers to the battle between Megamind and Metroman. The last, ‘you’ refers to Megamind. Then, Megamind responses Metroman’s threat by saying Oh, I am shaking in my custom baby seal-leather boot. The word ‘I’ refers to Megamind. From the explicature, Megamind responds may irrelevant.  But it conveys an implicature. There are many causes to make people shaking and that creates  the  implicated  premises; Megamind is  shaking because it is  cold; Megamind is shaking because of terrifying; Megamind is shaking just because he wants to; Megamind  is  shaking  just  because  he  pretends  to  be.  From the implicated premise.  It  may seem that  Megamind terrifies  being threatened by Metroman, but in reality Megamind does not fear at all. The intended meaning is he just pretending to be and mocking Metroman by showing his baby seal leather boot. Thus the implicated conclusion is Megamind does not fear of Metroman.The  writer  draws  conclusion  that  Relevance  Theory  is  concern  with ostensive communication that is intentional communication through an addressee that  can  understand  the  speaker’s  thought.  This  study hopefully  can  provide appropriate  references  for  further  researcher  to  conduct  the  research  in implicature. It is recommended for the next researchers to conduct similar studies to  be  analyzed  using  Relevance  Theory with  different  object  such  as  novel,  magazine or even article.